2017
DOI: 10.1186/s12872-017-0670-7
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction during anaphylaxis in a young healthy male with normal coronary arteries- is epinephrine the culprit?

Abstract: BackgroundAnaphylaxis is an acute, potentially fatal medical emergency. Myocardial injury or infarction in the setting of an anaphylaxis can be due the anaphylaxis itself, when it is known as Kounis syndrome or it can also be due to the effect of epinephrine treatment. Epinephrine is considered as the cornerstone in management of anaphylaxis. Myocardial infarction secondary to therapeutic doses of adrenaline is a rare occurrence and only a few cases have been reported in literature. The mechanism of myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Acute MI during anaphylactic reaction has been previously reported and may result from the anaphylaxis itself or from the epinephrine used to treat the anaphylaxis. 1 - 4 Kounis syndrome is the nonthrombogenic cause of myocardial ischemia or infarction triggered by the release of inflammatory mediators during an allergic or anaphylactic reaction. 11 The main pathophysiological pathway is thought to be the activation and degranulation of mast cells within the coronary arteries during these allergic reactions with release of chemical mediators like histamine and tryptase resulting in coronary vasospasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute MI during anaphylactic reaction has been previously reported and may result from the anaphylaxis itself or from the epinephrine used to treat the anaphylaxis. 1 - 4 Kounis syndrome is the nonthrombogenic cause of myocardial ischemia or infarction triggered by the release of inflammatory mediators during an allergic or anaphylactic reaction. 11 The main pathophysiological pathway is thought to be the activation and degranulation of mast cells within the coronary arteries during these allergic reactions with release of chemical mediators like histamine and tryptase resulting in coronary vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 It may result from the anaphylaxis itself or from the epinephrine used to treat the anaphylaxis. 1 - 6 While cases of MI due to large doses of intravenous epinephrine have previously been reported, MI after therapeutic doses of intramuscular epinephrine is rarely reported. 7 - 10 In this article, we present a case of acute MI in a young healthy patient after the use of intramuscular epinephrine for presumed anaphylaxis and review the literature for similar cases.…”
Section: Introductionmentioning
confidence: 99%
“…Although this treatment has been used safely for many years, there is a need for heart rate and ECG monitorisation in cases administered epinephrine consecutively [55]. It has been reported that MI has developed associated with epinephrine not only in cases with racemic epinephrine but also in cases where epinephrine has been used when applying cardiopulmonary resuscitation [56]. The coronary vasospasm of epinephrine is made over alpha 1 and alpha 2 receptors.…”
Section: Epinephrine Usementioning
confidence: 99%
“…While low-dose adrenaline shows a beta mimetic effect, at high doses the effect is seen by vasoconstriction, primarily over the alpha 1 and alpha 2 receptors. As there is a relationship between epinephrine used intravenously and a higher complication rate, the selection of intramuscular or subcutaneous routes could contribute greatly to reducing the cardiovascular risks [56] Vasodilators such as nitrate and calcium channel blockers are selected in MI cases related to epinephrine [57,58].…”
Section: Epinephrine Usementioning
confidence: 99%
“…1 Anaphylaxis is an immediate allergic reaction that has the propensity to cause severe coronary vasospasms. 2,3 Anaphylaxis virtually affects all major systems of the body including the cardiovascular system making the heart a target organ. 4 Kounis syndrome is a hypersensitivity coronary disorder induced by various allergens.…”
Section: Introductionmentioning
confidence: 99%